Trace Amine-Associated Receptor 5 Provides Olfactory Input Into Limbic Brain Areas and Modulates Emotional Behaviors and Serotonin Transmission - Espinoza, Stefano; Sukhanov, Ilya; Efimova, Evgeniya V.; Kozlova, Alena; Antonova, Kristina A.; Illiano, Placido; Leo, Damiana; Merkulyeva, Natalia; Kalinina, Daria; Musienko, Pavel; Rocchi, Anna; Mus, Liudmila; et al. (Frontiers in Molecular Neuroscience, 2020)
Trace amine-associated receptors (TAARs) are a class of G-protein-coupled receptors found in mammals. While TAAR1 is expressed in several brain regions, all the other TAARs have been described mainly in the olfactory epithelium and the glomerular layer of the olfactory bulb and are believed to serve as a new class of olfactory receptors sensing innate odors. However, there is evidence that TAAR5 could play a role also in the central nervous system. In this study, we characterized a mouse line lacking TAAR5 (TAAR5 knockout, TAAR5-KO) expressing beta-galactosidase mapping TAAR5 expression. We found that TAAR5 is expressed not only in the glomerular layer in the olfactory bulb but also in deeper layers projecting to the limbic brain olfactory circuitry with prominent expression in numerous limbic brain regions, such as the anterior olfactory nucleus, the olfactory tubercle, the orbitofrontal cortex (OFC), the amygdala, the hippocampus, the piriform cortex, the entorhinal cortex, the nucleus accumbens, and the thalamic and hypothalamic nuclei. TAAR5-KO mice did not show gross developmental abnormalities but demonstrated less anxiety- and depressive-like behavior in several behavioral tests. TAAR5-KO mice also showed significant decreases in the tissue levels of serotonin and its metabolite in several brain areas and were more sensitive to the hypothermic action of serotonin 5-HT1A receptor agonist 8-hydroxy-2-(di-n-propilamino)tetralin (8-OH-DPAT). These observations indicate that TAAR5 is not just innate odor-sensing olfactory receptor but also serves to provide olfactory input into limbic brain areas to regulate emotional behaviors likely via modulation of the serotonin system. Thus, anxiolytic and/or antidepressant action of future TAAR5 antagonists could be predicted. In general, “olfactory” TAAR-mediated brain circuitry may represent a previously unappreciated neurotransmitter system involved in the transmission of innate odors into emotional behavioral responses.